Deinagkistrodon acutus envenomation: a report of three cases - Cheng,Chin-Lung (2017)
Abstract Background Deinagkistrodon acutus envenomation is associated with severe hematological and wound complications but is rarely described. Case presentation Herein, we report three cases of victims bitten by D. acutus and indicate that rapid-onset severe coagulopathy and thrombocytopenia are distinct features of D. acutus snakebite, which are not observed in other crotaline snakebites (i.e., Trimeresurus stejnegeri and Protobothrops mucrosquamatus) in Taiwan. The toxic effects could occur as early as 2 to 3 h following D. acutus envenomation and persist if the administration of specific antivenom is delayed or even not commenced. Based on our findings, 2 to 4 vials of specific antivenom as the first dose should be administered to victims and repeated at 6 to 8 h intervals if coagulopathy or thrombocytopenia persists. Fresh frozen plasma or platelet replacement is probably safe as an adjunct therapy for D. acutus bite in the presence of venom-induced consumptive coagulopathy. Conclusion Severe coagulopathy and thrombocytopenia could occur as early as 2 to 3 h after D. acutus envenomation. The current recommendation for antivenom is 2 to 4 vials as the first dose and repeated every 6– to 8 h if coagulopathy or thrombocytopenia persists. These cases studied may be helpful to first-line medical personnel in the early diagnosis and management of D. acutus envenomation among other crotaline snakebites in Taiwan.